Effects of Global Warming on the Growth and Proliferation of Attached Sargassum horneri in the Aquaculture Area near Gouqi Island, China - Tingjian Wu; Lihua Xia; Minmin Zhuang; Jiayu Pan; Jinlin Liu; Wei Dai; Zitao Zhao; Meijing Zhang; Xiyu Shen; Peimin He; Jianheng Zhang; Yutao Qin (Journal of Marine Science and Engineering, 2022)
With global warming, in recent years, golden tides have frequently occurred off the coasts of China. Sargassum horneri, which attach to aquaculture rafts, can float and form small-scale golden tides after falling off. Temperature will affect the growth and reproduction of algae. In order to explore whether the temperature is the potential influence factor of the golden tide outbreak, in this study, the effects of global warming on the growth and proliferation of S. horneri in the mussel aquaculture area of Gouqi Island will be discussed. Samples of the macroalgae were collected monthly from August 2021 to July 2022 at various stages of its life cycle, and the relationship between algal growth and temperature was analyzed based on the concept of effective accumulated temperature, combined with the parameters of sea surface temperature, photosynthetic rate, growth rate, and growth cycle. Based on the continuous temperature variation observed, the growth cycle could be divided into five stages: the decreasing temperature period (October to November), the low-temperature adaptation period (December), the second suitable low-temperature period (January to February), and the high-temperature decay period (February to May). The effective accumulated temperature stored by S. horneri from 2021 to 2022 was 2772.4 °C·d; compared with previous studies, it decreased by about 800 °C·d. The winter temperature in 2022 was higher than the average temperature in the previous 5 years, allowing the macroalgae to enter the reproductive period in advance. This had a significant impact on the blooming time of golden tides and led to an earlier outbreak and extinction. Therefore, in the future, we can set up a monitoring system for the early warning of golden tides according to the change of SST in winter.